Penyuluhan Dan Simulasi Tanggap Gempa Untuk Peningkatan Kesiapsiagaan Guru Dan Siswa SDN 1 Jembatan Kembar Timur - Saidah, Humairo; Saadi, Yusron; Pradjoko, Eko; Ali, AM (Jurusan Teknik Mesin FT Universitas Mataram, 2025)
SDN 1 Jembatan Kembar Timur is located in West Lombok Regency, which is in a zone with a medium-high risk of earthquakes and tsunamis, so its residents must be prepared to face it, including schools that are gathering places for many young students who are at risk of panic during an earthquake. This community service activity aims to transfer information through counseling and earthquake simulations to train the preparedness of teachers and students. This activity was carried out using the counseling and simulation method, which was attended by teachers and grade 6 students. The results obtained from this activity were that teachers and students experienced increased knowledge and preparedness for earthquakes. The evaluation tool that measures the success of this activity shows an increase in knowledge of 30% at the end of the activity. A significant increase was especially shown in understanding what should be done during an earthquake when someone is in a class and a high building. This significant increase in knowledge of teachers and students is essential in advancing preparedness for earthquake disasters